Resilient Response of Cement-Treated Coarse Post-Glacial Soil to Cyclic Load - Katarzyna Zabielska-Adamska (MDPI AG, 2021)
Stabilisation with cement is an effective way to increase the stiffness of base and subbase layers and to improve the rutting of subgrade. The aim of the study is to investigate the effect of different percentages of cement additives (1.5%, 3.0%, 4.5% and 6.0%) on the resilient modulus of coarse-grained soil used on road foundations. The influence of the compaction method, the standard Proctor and the modified Proctor, as well as the sample curing time is analysed. The cement addition significantly increases the resilient modulus and reduces the resilient axial strain. Extending the curing time from 7 to 28 days also improves the resilient modulus. The change in the compaction energy from standard to modified does not increase the resilient modulus of the stabilised gravelly sand due to its compaction characteristics. The test results of the resilient modulus of the gravelly sand stabilised with cement indicate the possibility of using it as a material for the road base and subbase due to meeting the AASHTO requirements. However, the non-stabilised gravelly sand does not meet the above requirements. It has been sheared during cyclic tests at the first load sequence, regardless of the compaction method.